Knowledge Sharing Para Karyawan Minimarket: Perspektif Social Capital - Raharso, Sri; Tjahjawati, Sri Surjani (Jurnal Riset Bisnis dan Investasi, 2016)
The purpose of this paper is to investigate model that explores the influence of social capital (structural, relational, and cognitive social capital) on knowledge sharing. The survey was administered in minimarket at Bandung. Employees of the minimarket participated in the survey, 180 surveys were used to investigate a research model and hypotheses using factor analysis and multiple regression. The research confirmed the importance of social capital in the context of knowledge sharing. The paper provides empirical evidence that every social capital dimensions have a significant effect on knowledge sharing. Cognitive social capital has the strongest effect on employees’ knowledge sharing. Finally, there are inter-relationships among the dimensions of social capital.